The coevolution of money markets and monetary policy, 1815-2008 - Clemens Jobst; Stefano Ugolini (European Central Bank (ECB), 2014)
Money market structures shape monetary policy design, but the way central banks perform their operations also has an impact on the evolution of money markets. This is important, because microeconomic differences in the way the same macroeconomic policy is implemented may be non-neutral. In this paper, we take a panel approach in order to investigate both directions of causality. Thanks to three newly-collected datasets covering ten countries over two centuries, we ask (1) where, (2) how, and (3) with what results interaction between money markets and central banks has taken place. Our findings allow establishing a periodization singling out phases of convergence and divergence. They also suggest that exogenous factors – by changing both money market structures and monetary policy targets – may impact coevolution from both directions. This makes sensible theoretical treatment of the interaction between central bank policy and market structures a particularly complex endeavor.
Keywords: E52; G15; N20; 330; Central Banking; monetary policy implementation; money markets; Geldmarkt; Geldpolitik; Zentralbank; Europa; USA